Leaf shape, planting density, and nitrogen application affect soybean yield by changing direct and diffuse light distribution in the canopy - Zhao, Wei; Ren, Ting-Hu; Huang, Xin-Yang; Xu, Zheng; Zhou, Yan-Zheng; Yin, Cheng-Long; Zhao, Rui; Liu, Sheng-Bo; Ning, Tang-Yuan; Li, Geng (Plant physiology and biochemistry, 2023)
When attempting to maximize the crop yield from field-grown soybean (Glycine max (L.) Merr.) by means of improving the light conditions for photosynthesis in the canopy, it is crucial to find the optimal planting density and nitrogen application rate. The soybean plants that were the subject of our experiment were cultivated in N-dense mutual pairs, and included two cultivars with different leaf shapes; one cultivar sported ovate leaves (O-type) and the other lanceolate leaves (L-type). We analyzed the results quantitatively to determine the amount of spatial variation in light distribution and photosynthetic efficiency across the canopy, and to gauge the effect of the experimental parameters on the yield as well as the photosynthetic light and nitrogen use efficiency of the crop. Results indicate that the different leaf shapes were responsible for significant disparities between the photosynthetic utilization of direct and diffuse light. As the nitrogen fertilizer rate and the planting density increased, the soybean plants responded by adjusting leaf morphology in order to maximize the canopy apparent photosynthetic light use efficiency, which in turn affected the leaf nitrogen distribution in the canopy. Despite the fact that the light interception rate of the canopy of the L-type cultivar was lower than that of the canopy of the O-type cultivar, we found its canopy apparent photosynthetic nitrogen and light use efficiency were higher. It was interesting to note, however, that the nitrogen and light use efficiency contributions associated with exposure to diffuse light were greater for the latter than for the former. •The significant decrease in light intensity at the bottom of the canopy correlates significantly with direct light.•The light and nitrogen use efficiency is higher with diffuse light, especially within the O-type canopy.•The contribution of diffused light at the bottom of the O-type canopy cannot be ignored.•Nitrogen has a significant effect on L-type, which are suitable for high-density planting and nitrogen should be applied.